(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2014)
Present study was conducted at Tigris river, near Wasit Thermal Power Plant (WTPP) in Al Zubiadiyah city to evaluate the impact of discharging domestic sewage during construction period(2010-2016) on water quality of the river; to assess the level at which effluents discharged from WTPP affect the quality of Tigris river water; and to compare the quantity of pollutants in the water with the acceptable limits of Iraqi Standards. Observation recorded during the three months study depicted that the river is polluted in certain areas downstream the river as comparatively higher values of biological oxygen demand (BOD) and chemical oxygen demand (COD) were recorded. The level of total dissolved solids (TDS), dissolved oxygen (DO), chemical oxygen demand (COD), biological oxygen demand (BOD), total hardness, sodium ion, and sulfates (SO4) in the water sample were quite high. With the exception of pH, all other physical-chemical parameters measured are between 100% and 180% higher and have exceeded the maximum permissible limit given by the permissible Iraqi standards. The domestic wastewater is discharged directly to river without any treatment during this period (construction period), there is tendency of these pollutants to persist in the water and its uptake may cause long term health problems when the water is used as drinking water, especially in areas near the point of discharge, since there is an intake of a water compact unit 1 km downstream from the point of discharge (Al-Bokhauder village ), as well as the adverse effects on plants when the contaminated water used for plant irrigation .